Pengaruh Senam Yoga Terhadap Perubahan Gula Darah Pada Pasien Diabetes Mellitus Tipe II di Wilayah Kerja Puskesmas Cakranegara Mataram tahun 2018 - Rukmana, Siti Hardianti; Hadi, Irwan; Suprayitna, Marthilda (Jurnal Kesehatan Qamarul Huda, 2018)
Diabetes Mellitu (DM ) is a disease that is exposed by the interaction of various factors : genetic, immunologic, environmental, and lifestyle. Lack of physical activity, stress and anincreasing old age resulted in reduced insulin will decrease because the function of pancreas decreased, than exercise is recommended to control blood sugar levels, one of which is yoga exercise. This study aims to determine the effect of yoga on changes blood sugar levels in patients with diabetes mellitus type II in Working Area Of Cakra Negara Public Health Center. This research is Quasy Xperiment with pre and post without control approach. The samples in this research were 10 people with DM in Cakra Negara Public Health Center. Result of T test analysis (Paired Sample) obtained p = 0,006 < 0,05. It can concluded that there is an effect of gymnastic yoga toward blood sugar levels changes in patient with DM type II in Cakra Negara public health center, frpm this research hoped for health services in order to be a motivator for people with DM to do gymnastic yoga to control blood sugar levels and prevent complication.